The Depths of the Human Soul: Freud's Deconstruction and the Reconstruction of the Spirit in the Book of Sirr al-Asrar - Dewi Masita; Khabibah Khabibah (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2025)
This study explores the complexity of the human psyche through hermeneutical methods, while reexamining Freud's psychological map with a deconstructive approach. The structure of the id, ego, and superego is reexamined, and the concept of the soul is reformulated based on Abdul Qadir al-Jilani's Sirr al-Asrar. This literature research relies on primary sources, particularly Freud's works and texts from Sirr al-Asrar. The findings indicate that Freud's structure of the soul is limited to a psychodynamic understanding, while Sirr al-Asrar offers a spiritual dimension as a center of consciousness capable of addressing the existential challenges of today. The hermeneutic approach opens up a richer perspective on the psychological dynamics of modern humans. This research report makes an important contribution to the field of psychospirituality and contemporary psychotherapy practices.